Effect of mushroom supplementation as a prebiotic compound in super worm based diet on growth performance of red tilapia fingerlings - Abd Rahman Jabir Mohd Din; Shaharudin Abdul Razak; Vinikeswary Sabaratnam (Universiti Kebangsaan Malaysia, 2012)
A feeding trial was conducted to investigate the effect of mushroom supplementation as a prebiotic compound in an insect-based diet on the growth performance and feed utilization of red Tilapia (Oreochromis sp.). A total of 120 fingerlings were divided in triplicates for each treatment. Four experimental diets were offered to the fishes within a 56 days treatment period. Out of the four diets, three contained mushroom stalk meal (MSM) supplementation at various levels of inclusion of prebiotic compound (0.5% MSM; 1.0% MSM; 1.5% MSM) and the fourth a control diet without MSM inclusion. During the growth test, fish receiving diet containing prebiotic showed significantly higher (p<0.05) mean individual body weight in comparison with the control diet. The best effect was obtained in fish fed with Diet 2, where the specific growth rate (SGR) was 1.74%, feed conversion ratio (FCR) was 0.58, protein efficiency ratio (PER) was 5.17 and survival was 93.33%. No significant differences (p>0.05) were observed in whole body protein and ash contents among the fish feeding on these diets. All water quality parameters showed no significant difference (p>0.05) in all treatments. The result of this feeding trial indicated that the 10% supplementation level of MSM as a prebiotic for tilapia could be used in the insect-based diet, Zophobas morio.